Effects of Shoot Size and N6-benzyladenine Concentration on Shoot Organogenesis of Phut Nam - ดำยศ เปรมฤดี; ชูสิริ เบญจวรรณ; เตชะวรรักษ์ กาญจนี (Journal of Vocational Education in Agriculture, 2019)
The objective of this research was to investigate the effects of shoot size and benzyladenine concentration on shoot organogenesis of Phut Nam [Kailarsenia hygrophila (Kurz) Tirveng.]. The fruit explants were flame sterilized by dipping them in 95% alcohol followed by flaming. These explants were cultured on Murashige and Skoog (MS) medium without plant growth regulator for 2 weeks and were 100% free from contamination. The culturing shoot explants at 1 and 2 cm in length were placed on MS medium supplemented with N6-benzyladenine (BA) at concentration of 1, 3 and 5 mg/L. The experiment separated two-factor factorial with completely randomized design (CRD), 5 replications. After 8 weeks in culture, it was found that the 1 cm shoot length or medium containing 3 mg/L BA showed the greatest number and height of new shoots and nonsignificant in interaction between shoot size and BA concentration. The excised stems from shoot cultured were placed on MS medium without or containing 0.25 and 0.5 mg/L -napthalenacetic acid (NAA) for root induction. After for 6 weeks in culture, stem explants gave the highest root formation, number and lengths on medium without NAA.